Perencanaan Kurikulum PAI dalam Neningkatkan Mutu Guru di SMP IT Al-Afkary - Rahmawati, Nelly; Sopian, Sopan; Berutu, Riswan (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research focuses on curriculum planning in improving the quality of PAI teachers at SMP IT Al-Afkary. The purpose of this study was to analyze the PAI curriculum planning process at SMP IT Al-Afkary. the type used is descriptive qualitative research, namely data collected in the form of interviews, documents and so on. The results of this study indicate that the PAI curriculum management at Al-Afkary IT Middle School implements it in accordance with the vision and mission that has been previously determined because the development of noble character in students and learning Islam is a goal that is closely related to each other. The teacher manages PAI classes at the curriculum level by making lesson plans, carrying out lessons, and evaluating the learning.